Effect of nano silica and coir fiber on compressive strength and abrasion resistance of Concrete. (30th November 2019) - Gupta, Mayank; Kumar, Maneek
Highlights: Coir fiber has been added with the variations of 0.25%, 0.5%, and 0.75% by the weight of the fine aggregates, along with this 2% and 3% nano-silica and 15% fly ash has partially replaced cement in the matrix. Addition of coir fiber and nano silica enhanced the compressive strength but had an inverse effect on the workability and abrasion resistance. Rate of increment in the 7 days compressive strength is comparatively higher than the 28 days. Inclusion of Nano silica and Fly Ash fills the existing voids of concrete and make the concrete denser. Formation of coir lumps is one of the major reasons for reduction in the compressive strength of concrete. Abstract: This research investigates the effect of nano silica and coir fiber on compressive strength and abrasion resistance of concrete. In this study, Coir fiber has been added in the concrete with the variation of 0.25%, 0.5%, and 0.75% by the weight of the fine aggregates and 2% and 3% nano silica along with 15% fly ash which has partially replaced cement in the concrete mixture. Different samples with varying percentages of nano silica and coir fiber have been prepared to keep water to binder ratios like 0.47, 0.45 and 0.42 for calculating the compressive strength and abrasion resistance and results have been compared with the controlled specimens. It is reported that the optimum dosage of coir fiber and nano silica is 0.25% and 3%, respectively which provides approximate equal abrasion resistance as compared to the conventional concrete sample.